"POSSIBILITIES OF USING THE EXPERIENCE OF SINGAPORE IN THE DEVELOPMENT OF ELECTRONIC GOVERNMENT SERVICES IN UZBEKISTAN" (Web of Teachers: Inderscience Research, 2024)
State services based on artificial intelligence technologies have been introduced in Uzbekistan in order to improve the lives of citizens, make public services efficient and make the country a leader in the digital economy. As part of the government's "Digital Uzbekistan 2030" strategy, SI technologies are widely used and aimed at creating innovative solutions in various fields. Through these technologies, public services are becoming faster, more efficient and more convenient for citizens. The implementation of artificial intelligence (AI) technologies in e-government services will significantly change the management system and increase its efficiency. The following is a detailed account of how the use of SI in the case of Singapore can change the governance system: